2009
DOI: 10.1007/s11420-009-9108-9
|View full text |Cite
|
Sign up to set email alerts
|

A Musculoskeletal Profile of Elite Female Soccer Players

Abstract: The purpose of this study is to identify lowerextremity (LE) musculoskeletal characteristics of elite female soccer players and to determine whether differences between dominant and nondominant extremities exist with respect to strength, flexibility, and range of motion. Physical data were collected from 26 female professional soccer players. Core control, hip and knee passive range of motion (PROM), LE flexibility, hip abductor strength, and dynamic functional alignment were assessed for each LE. Of 26 subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
2
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 27 publications
1
17
2
1
Order By: Relevance
“…Three studies measured the effects of femoroacetabular impingement (FAI), 15,24,25 1 study measured the effects of hip chondropathy (HC), 28 and 2 studies measured the effects of hip arthroscopy surgery 14,26 on squat performance (Table 2). Two studies examined the effects of muscle pain, 27,29 5 studies measured the effects of muscle fatigue, [30][31][32][33][34] and 2 studies reported the effects of muscle tightness 35,36 on squat performance ( Table 3). All qualifying manuscripts yielded a total of 542 subjects (160 men and 382 women; mean age = 29.3 (5.9) y) and measured performance with either the barbell squat, step down, bilateral, or single-leg squat.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Three studies measured the effects of femoroacetabular impingement (FAI), 15,24,25 1 study measured the effects of hip chondropathy (HC), 28 and 2 studies measured the effects of hip arthroscopy surgery 14,26 on squat performance (Table 2). Two studies examined the effects of muscle pain, 27,29 5 studies measured the effects of muscle fatigue, [30][31][32][33][34] and 2 studies reported the effects of muscle tightness 35,36 on squat performance ( Table 3). All qualifying manuscripts yielded a total of 542 subjects (160 men and 382 women; mean age = 29.3 (5.9) y) and measured performance with either the barbell squat, step down, bilateral, or single-leg squat.…”
Section: Resultsmentioning
confidence: 99%
“…All qualifying manuscripts yielded a total of 542 subjects (160 men and 382 women; mean age = 29.3 (5.9) y) and measured performance with either the barbell squat, step down, bilateral, or single-leg squat. 14,15,[24][25][26][27][28][29][30][31][32][33][34][35][36] Several studies also included other measures of performance that are described in Tables 2 and 3. 24,28,29,33,36 The following sections discuss the results of this analysis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations